2002
DOI: 10.1016/s0006-3495(02)75506-9
|View full text |Cite
|
Sign up to set email alerts
|

Unzipping DNA with Optical Tweezers: High Sequence Sensitivity and Force Flips

Abstract: Force measurements are performed on single DNA molecules with an optical trapping interferometer that combines subpiconewton force resolution and millisecond time resolution. A molecular construction is prepared for mechanically unzipping several thousand-basepair DNA sequences in an in vitro configuration. The force signals corresponding to opening and closing the double helix at low velocity are studied experimentally and are compared to calculations assuming thermal equilibrium. We address the effect of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
264
1
7

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 275 publications
(283 citation statements)
references
References 33 publications
7
264
1
7
Order By: Relevance
“…These data cover the complete range of forces that can be expected for unfolding DNA. Previous work on phage DNA found that kilobase-long duplexes with Ϸ50% GC content unzip at an average force of Ϸ15 pN (23)(24)(25). Our results indicate that this asymptotic value is reached at a duplex length of only Ϸ25 bp.…”
Section: Resultssupporting
confidence: 56%
See 1 more Smart Citation
“…These data cover the complete range of forces that can be expected for unfolding DNA. Previous work on phage DNA found that kilobase-long duplexes with Ϸ50% GC content unzip at an average force of Ϸ15 pN (23)(24)(25). Our results indicate that this asymptotic value is reached at a duplex length of only Ϸ25 bp.…”
Section: Resultssupporting
confidence: 56%
“…Especially useful is the fact that the location of the transition state along the reaction coordinate can be derived directly from the force dependence of the kinetic rates (21). The application of force also facilitates the study of molecules with a wide range of energetic stabilities under similar environmental conditions, as demonstrated by the force-induced unfolding of short duplexes (22) and hairpins (20) and very long duplexes (23)(24)(25). Nanomechanical measurements have been used to follow folding transitions in single and multiple hairpins of DNA (26) and RNA (27)(28)(29)(30), but no attempt has yet been made to investigate systematically the effects of sequence on the folding process.…”
mentioning
confidence: 99%
“…Previously, there have been a number of experimental and theoretical studies (9)(10)(11)(12) on the effect of sequence heterogeneity on DNA melting and unzipping transitions. Our study is along this general direction.…”
mentioning
confidence: 99%
“…For example, the energy landscape of the DNA helix was explored by unzipping dsDNA molecules. 63 Digoxigenin and biotin tags on adjacent overhangs of dsDNA were used to attach one strand to a bead and the other to a slide surface, which was then moved away from the trap. The DNA unzipping force was measured by tracking bead displacement from the beam focus.…”
Section: Optical Tweezers (Ot)mentioning
confidence: 99%